2020
DOI: 10.1093/tas/txaa230
|View full text |Cite
|
Sign up to set email alerts
|

Soybean molasses to replace corn for feedlot lambs on growth performance, carcass characteristics, and meat quality

Abstract: Soybean molasses (SBM) is a byproduct of the manufacture of soy protein concentrate and has high energy value. This byproduct has a high potential for use in the nutrition of ruminant animals, mainly in the replacement of other energy feeds such as corn grain. The objective of this study was to evaluate the inclusion of SBM to replace corn grain up to 30% dry matter (DM) in the total diet on growth performance, feeding behavior, carcass characteristics, and meat quality of feedlot lambs (½ Santa Inês × ½ Dorpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In our work, it was possible to characterize these chemical and biochemical properties in the cyanobacterial biomass and the LTPNA 01 strain. Therefore, given their nutritional composition and the absence of microcystins in samples, they may be recommended for use as an additive in animal feed (especially for small ruminant animals,), thus contributing to their nutritional supply (e.g., lipids, ash, proteins, and carbohydrates) [35,36]. In a recent study, the addition of increasing doses of marine microalgae (Schizochytrium) meal up to 6% of the total diet in Ile de France lambs was evaluated [37].…”
Section: Discussionmentioning
confidence: 99%
“…In our work, it was possible to characterize these chemical and biochemical properties in the cyanobacterial biomass and the LTPNA 01 strain. Therefore, given their nutritional composition and the absence of microcystins in samples, they may be recommended for use as an additive in animal feed (especially for small ruminant animals,), thus contributing to their nutritional supply (e.g., lipids, ash, proteins, and carbohydrates) [35,36]. In a recent study, the addition of increasing doses of marine microalgae (Schizochytrium) meal up to 6% of the total diet in Ile de France lambs was evaluated [37].…”
Section: Discussionmentioning
confidence: 99%
“…Lamb consumers demand fresh, tasty, safe, and microbe-free meat with high eating quality and nutrient content, thus necessitating advanced nutrition and breeding strategies that integrate appropriate meat quality characteristics by sheep producers ( 4 ) to improve feedlot performance, dressing percentage, lean yield, and marbling score ( 5 , 6 ). To achieve accelerated lamb growth and early attainment of appropriate slaughter weights that meet market specifications, feedlotting remains a critical lamb finishing strategy for improving profitability ( 7 , 8 ). It also facilitates the production of more uniform lamb carcasses ( 9 ) from a low mortality system that ensures more efficient use of human and technical resources to attain improved meat yield and quality ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of SM in the diet did not influence animal feed intake and performance, which indicates the by-product is a viable feedstuff in ruminant nutrition that can be used as a macro-ingredient substitute for corn in feedlot diets without causing rejections and declines in animal productivity. Arruda et al (2021) and Rodrigues et al (2020) evaluated SM inclusions of up to 30% in the DM of the diet and observed no effects on lamb feed intake and performance. Previous reports indicate that SM-containing diets have a higher digestibility ( Pereira Junior et al, 2018 ; Arruda et al, 2019 ), an effect that may be attributed to the carbohydrate solubility that SM adds to the diet (35.1—CON vs. 230.8 g kg -1 SM20 of soluble carbohydrates).…”
Section: Discussionmentioning
confidence: 99%